2018
DOI: 10.1038/s41598-018-26674-0
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing auranofin as an intestinal decolonizing agent for vancomycin-resistant enterococci

Abstract: Multidrug-resistant enterococcal pathogens, especially vancomycin-resistant enterococci (VRE), are among the pathogens that require new antibiotic innovation. The colonization of the gut represents a major pathway by which VRE can cause infection and spread to other patients. In the current study, auranofin (FDA-approved rheumatoid arthritis drug) is evaluated for its potential use as a decolonizing agent for VRE. Auranofin was found to exert potent antimicrobial activity against a wide range of enterococcal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…Auranofin is an FDA-approved, gold-containing, drug used to treat rheumatoid arthritis. Previous studies on auranofin have reported that the drug possesses potent antibacterial activity against clinically-pertinent pathogens including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), and Clostridioides difficile [15][16][17][18][19][20] . However, no reports have investigated the effect of auranofin against N. gonorrhoeae.…”
mentioning
confidence: 99%
“…Auranofin is an FDA-approved, gold-containing, drug used to treat rheumatoid arthritis. Previous studies on auranofin have reported that the drug possesses potent antibacterial activity against clinically-pertinent pathogens including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), and Clostridioides difficile [15][16][17][18][19][20] . However, no reports have investigated the effect of auranofin against N. gonorrhoeae.…”
mentioning
confidence: 99%
“…Auranofin is an FDA-approved anti-rheumatoid arthritis drug, with a well-studied safety profile for human use 16,17 . Recently, auranofin has gained interest in repurposing for treatment of bacterial and parasitic infections [18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…Furthermore, it is undergoing Phase II clinical trials for the treatment of amoebic dysentery, giardiasis (NCT02736968) and tuberculosis (NCT02968927). Auranofin possesses strong antibacterial and antifungal activities 17,[22][23][24][25] . We previously demonstrated that auranofin has a potent anticlostridial activity with strong inhibition of both toxins and spores production in vitro 24 .…”
mentioning
confidence: 99%
“…Drug repositioning is a promising field that investigates new therapeutic opportunities for existing approved drugs with readily available information on their pharmacokinetic profile, dosages, and toxicity to humans (14)(15)(16)(17)(18)(19). This approach can significantly reduce the total cost, time, and effort to develop novel antibacterial agents.…”
mentioning
confidence: 99%